Molecular Genetic Characterization of Different Accessions of Centella Asiatica - Wong, Sook Mun (2003)
Centella asiatica or locally known as "pegaga" belongs to the Apiceae family. This medicinal plant is one of the most important medicinal herbs, and widely used in health foods, pharmaceutical and cosmetic industries. Twelve accessions of C. asiatica planted in MARDI, originated from different locations in Peninsular Malaysia, were used for this study. Phenotypic differences among these accessions are not very distinct, thus this study is undeitaken to determine whether there are any genetic differences. DNA markers, unaff ected by environmental or physiological factors, have potential utility in the characterization of plant species. High discriminating power of this class of markers demonstrated uniformity and stability within genetically complex cultivars. Good quality DNA was extracted from leaf samples using conventional hexadecyltrimethylammonium bromide (CTAB) method. Two PeR-based DNA markers system. namely Amplified Fragment Length Polymorphisms (AFLPs) and Long Primer Randomly Amplified Polymorphic DNA (LP-RAPDs), were employed. This study has successfully analyzed the genetic relationships among the accessions of C. asiatica. Two phylogenetic trees bad been constructed from the unweighted pair group method with arithmatical average (UPGMA) pairwise analyses. Genetic distances was calculated based on. the Dice similarity index. From both analyses, the CA01 and CA02 as wen as CA05 and CA06 were closer (D=0.119) within the same cluster indicating that they are closely related. Based on the genetic distances, CA10 represented as highest distant group in the LP-RAPDs analyses whereas CA03 represented as highest distant group in the AFLPs analyses. Furthermore, diagnostic band with highest molecular weight (3000 bp) was found in CA10 by using long primer PEH A3. The amplification of CA03 genotypes with AFLP primer pair ACG/CTA has shown a unique DNA profile. In addition, CA03 is easily distinguish from other accessions morphologically due to its wavy shape of the plant leaf.